Synthesis and X‐ray structural characterization of a bidendate phosphine (dppe) palladium(II) complex and its application in Stille and Suzuki cross‐coupling reactions. (24th July 2016) - Naghipour, Ali; Ghorbani‐Choghamarani, Arash; Babaee, Heshmatollah; Notash, Behrouz
Abstract : The synthesis, characterization, crystal structure and catalyst activity of the bidentate phosphine complex [1, 2‐bis(diphenylphosphino)ethane]palladium(II) bromide, [PdBr2 (dppe)], are presented. Treatment of 1, 2‐bis(diphenylphosphino)ethane with palladium(II) bromide under mild conditions resulted in the compound in high yield and purity. The characterization of the synthesized compound was performed using spectroscopic methods, such as Fourier transform infrared and NMR, CHN analysis and X‐ray crystallography. The structure of the compound was slightly distorted square planar. This compound was found to work as an efficient catalyst for both Stille andSuzuki cross‐coupling reactions of various aryl halides with triphenyltin chloride and/or phenylboronic acid. Also, the catalyst could be recovered and reused several times without significant loss of itscatalytic activity . Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The bidentate phosphine complex [1, 2‐bis(diphenylphosphino)ethane]palladium(II) bromide, [PdBr2 (dppe)], synthesized and it's crystal structure reported. It's catalytic activity in both Stille and Suzuki cross‐coupling reactions of various aryl halides with triphenyltin chloride and/or phenylboronic acid, reported.